2021
DOI: 10.1108/nfs-07-2021-0227
|View full text |Cite
|
Sign up to set email alerts
|

Stunting and its associated factors in children aged 6–59 months in Ilubabor zone, Southwest Ethiopia

Abstract: Purpose Stunting, which refers to low height-for-age, is one of the most important public health problems in Ethiopia, and it more accurately reflects nutritional deficiencies and illness that occur during the most critical periods for growth and development in early life. Given this, this paper aims at determining the magnitude and factors associated with stunting among 6–59 month old children in Ilubabor Zone, Southwest Ethiopia. Design/methodology/approach This paper opted for a descriptive study using an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
1
1
0
Order By: Relevance
“…This finding is consistent with the study conducted in Woldia northeast Ethiopia (14), and Welfare Monitoring Survey of Ethiopia, 2011 (38). It is an inevitable reality that as the number of family members increases, it becomes more difficult for them to provide adequate and diverse food to meet everyone's needs (39). As a result, the parent prioritizes and focuses solely on meeting daily needs rather than dietary quality.…”
Section: Discussionsupporting
confidence: 88%
“…This finding is consistent with the study conducted in Woldia northeast Ethiopia (14), and Welfare Monitoring Survey of Ethiopia, 2011 (38). It is an inevitable reality that as the number of family members increases, it becomes more difficult for them to provide adequate and diverse food to meet everyone's needs (39). As a result, the parent prioritizes and focuses solely on meeting daily needs rather than dietary quality.…”
Section: Discussionsupporting
confidence: 88%
“…Nigeria, Indonesia and India), the prevalence of stunting in children under five years exceeds 30% (Menon et al , 2018; Olusanya et al , 2010; Hanifah et al , 2018) and some studies have even reported the prevalence of stunting to be as high as 52.1% (Linasari, 2021) and 80% (Kohlmann et al , 2021). In addition, a recent study among Southwest Ethiopian children also report the prevalence of stunting to be more than 30% (Zewdie et al , 2021). Undernutrition in young children is a problem of public health importance in most developing countries, accounting for significant morbidity and mortality.…”
Section: Discussionmentioning
confidence: 99%